Proceedings of the 26th Australian Computer-Human Interaction Conference on Designing Futures: The Future of Design 2014
DOI: 10.1145/2686612.2686639
|View full text |Cite
|
Sign up to set email alerts
|

Exploration without keywords

Abstract: As a generation of information seekers we tend to think in terms of targeted search results, yet there are some contexts in which a more exploratory behaviour might be desirable. This paper presents the design and development of a playful Web app called Bookfish that seeks to encourage exploratory behaviour amongst children wishing to discover new books. Bookfish sets out to return more open, or even unexpected, serendipitous results through using an approach designed for exploration rather than search. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Semantic addressing is designed specifically to make it easier for information seekers to find other books that may pique their interest (Svenonius, 2000). In view of this, various digital tools have emerged to attempt to facilitate IE within the limited scope of the digital library (e.g., Kleiner et al, 2013;Pearce & Chang, 2014;Thudt et al, 2012). Although these tools have not been investigated in terms of whether and how users leverage the encountered information, McCay-Peet has shown that digital tools can influence IE .…”
Section: Influencing Information Encounteringmentioning
confidence: 99%
“…Semantic addressing is designed specifically to make it easier for information seekers to find other books that may pique their interest (Svenonius, 2000). In view of this, various digital tools have emerged to attempt to facilitate IE within the limited scope of the digital library (e.g., Kleiner et al, 2013;Pearce & Chang, 2014;Thudt et al, 2012). Although these tools have not been investigated in terms of whether and how users leverage the encountered information, McCay-Peet has shown that digital tools can influence IE .…”
Section: Influencing Information Encounteringmentioning
confidence: 99%
“…Comparing Search and Browsing: One explanation for co-borrowing is that users may identify books individually in search and select them independently of one another. While early studies [32,33] do not support this, the increasing dominance of search [23,28] suggests that search could be responsible for these results. We created a stop-worded log-rule search index [37] for the titles of the books (the only metadata we had, but data that is frequently used in book search [11,24,38]).…”
Section: Day Of the Week Effectsmentioning
confidence: 93%
“…Earlier work suggests browsers check 'three shelves before and after' a target book-this is something in the range of 200-500 books. This is considerably more books than are typically shown in search results, and an order of magnitude more than is shown in some nascent browsing systems [23]. Research on recommender systems has shown that a few 'unexpected' recommendations improve user experience [39].…”
Section: Shelf Topic and Searchmentioning
confidence: 97%
See 2 more Smart Citations